A Schumpeterian Model of Top Income Inequality - Jones, Charles I.; Kim, Jihee (Journal of Political Economy, 2018)
Top income inequality rose sharply in the United States over the last 40 years but increased only slightly in France and Japan. Why? We explore a model in which heterogeneous entrepreneurs, broadly interpreted, exert effort to generate exponential growth in their incomes, which tends to raise inequality. Creative destruction by outside innovators restrains this expansion and induces top incomes to obey a Pareto distribution. Economic forces that affect these two mechanisms—including information technology, taxes, and policies related to innovation blocking—may explain the varied patterns of top income inequality that we see in the data.